Oil Pollution and its Impact on the Environment in Iraq - Mohammed, Mustafa Riyadh Matnee; Mohammed, Iyadh Matnee; Abtan, Sajjad Abdul-Razzaq Hassani; Ali, Amenah Fawwaz Mohamed; Jasim, Karar Mohammed Mohsin (American Journal of Botany and Bioengineering, 2025)
Oil pollution remains a critical environmental challenge in Iraq, significantly affecting air, water, and soil quality. Despite Iraq’s extensive oil production history, there is a knowledge gap regarding the long-term ecological and health consequences of oil contamination. This study employs a comprehensive analysis of pollution sources, environmental impacts, and mitigation strategies through case studies and regulatory assessments. Findings indicate that oil spills, industrial waste, and military conflicts have led to severe degradation of marine and terrestrial ecosystems, posing risks to biodiversity and public health. The results emphasize the urgent need for stricter environmental policies, improved enforcement mechanisms, and sustainable technological solutions to mitigate pollution and restore affected environments.